Investigation of the morphological cell structures and their optical significances of Aeshna cyanea - Juliet Sackey; Zebib Yenus Nuru; Nkosi Mlungisin; Malik Maaza (IET Nanobiotechnology, 2019)
The transparent wing of the dragonfly Aeshna cyanea has been investigated using scanning electron microscopy (SEM), optical microscopy (OPM), energy‐dispersive X‐ray spectroscopy (EDS) and reflectance spectroscopy. Four cells (D1–D4) were studied and classified according to their general morphology. The OPM depicted the vein‐joint characterised by the distribution of resilin. EDS technique showed common elements such as carbon, oxygen, and chlorine. SEM analysis revealed thin membranes reinforced with a network of hallow veins. Spikes and round shape of microstructures were identified. The roughness of the pruinosity was estimated, which indicates the shape and curvature of the microstructures that essentially play a significant role in the optical response observed. The study can be essential to design and improve micro‐air vehicles.